1998
DOI: 10.1098/rspb.1998.0498
|View full text |Cite
|
Sign up to set email alerts
|

A female nervous system is necessary for normal sperm storage in Drosophila melanogaster: a masculinized nervous system is as good as none

Abstract: A male Drosophila melanogaster deposits many more sperm in a female's bursa copulatrix than are stored in her ventral receptacle or paired spermathecae soon after copula has ended. The remaining sperm are expelled by the female. These observations suggest a sexual con£ict over the processes involved in sperm storage. We used genetically manipulated £ies to study the role of the central nervous system in sperm storage. Flies with female bodies but masculinized nervous systems, or isolated female abdomens, store… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
34
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 22 publications
4
34
0
Order By: Relevance
“…Given the distance that sperm must travel to reach the spermathecae, it is unlikely that ejaculate transport and displacement could be facilitated without the active participation of the female. Similar patterns of female involvement in sperm transport have been described for other dipterans (Gilbert 1981;Otronen & Siva-Jothy 1991;Arthur et al 1998), and implicated in S. stercoraria (Ward 1993). However, the question of whether females actually bene¢t from sperm displacement has not yet been addressed.…”
Section: Introductionmentioning
confidence: 75%
“…Given the distance that sperm must travel to reach the spermathecae, it is unlikely that ejaculate transport and displacement could be facilitated without the active participation of the female. Similar patterns of female involvement in sperm transport have been described for other dipterans (Gilbert 1981;Otronen & Siva-Jothy 1991;Arthur et al 1998), and implicated in S. stercoraria (Ward 1993). However, the question of whether females actually bene¢t from sperm displacement has not yet been addressed.…”
Section: Introductionmentioning
confidence: 75%
“…Previous studies have demonstrated that an intact female nervous system is required for proper sperm storage in Drosophila: as females with masculinized nervous systems showed abnormal sperm storage (Arthur et al 1998). In Tribolium beetles, isolated female abdomens showed abnormal sperm storage, also suggesting the need for nervous system input (Bloch Qazi et al 1998).…”
Section: Discussionmentioning
confidence: 95%
“…Genetic mosaics have been used to show that the response to seminal proteins requires a female nervous system (Arthur et al, 1998). The results beg the question of molecular mechanisms that may cause these differences.…”
Section: Females Play An Active Role In Sperm Usementioning
confidence: 99%